Analysis of the relationship between the prices of wheat and rice importer in Iraq and crude oil prices and the exchange rate using the ARDL model - العبدلي سعد عبد نجم; سليمان هيفاء يوسف (Journal of Economics and Administrative Sciences, 2025)
Since the beginning of 21st century, the prices of Agricultural crops have increased. This Increases is accompanied with that increases of crude oil prices and fluctuation of a dollar exchange rate as a dominant currency used in the global trade. The paper aimed to analysis the short run and long run cointegration relationships between prices of some of Agricultural crops imported by Iraq such as wheat and rice crops and both the crude oil prices and the Iraq dinar exchange rate a gained America dollar using ARDL model. The results show the long run equilibrium between they three variable throng the error correction mechanizem. The results also show the significant and economically sound effects of crude oil prices and the exchange rate as explanatory variables of the prices of wheat and rice imported by Iraqi officials